The interplay between gastrointestinal and cardiovascular diseases: a narrative review focusing on the clinical perspective. Issue 2 (8th June 2020) - Sbeit, Wisam; Kadah, Anas; Mahamid, Mahmud; Mari, Amir; Khoury, Tawfik
Abstract : Both cardiovascular and gastrointestinal disorders represent considerable health burden on community clinics and hospitals with overwhelming economic cost. An overlap in the occurrence of these disorders is encountered in daily practice. Both affect each other in bidirectional manner through several mechanisms including altered hemodynamics, systemic inflammation, bacterial overgrowth and interactions and adverse effects of medications. In addition, to the known overlap in the symptoms occurrence of upper gastrointestinal tract diseases and cardiovascular diseases (CVDs). Awareness of this interplay and its clinical manifestations optimizes patient management, and could prevent catastrophic consequences and even save lives. In this review, we highlighted the clinical aspects of this bidirectional association between gastrointestinal and CVDs aiming to shed light on this topic and improve patients' care.